Trials and tribulations: a qualitative exploration of researcher perspectives on navigating the challenges of health system implementation research - Natalie Taylor; April Morrow; Julia Steinberg; Emily Hogden; Deborah Debono; Elijah Tyedmers; Priscilla Chan; Gabriella Tiernan (BMJ Open)
Objective While researchers are crucial to the successful delivery of implementation trials, their perspectives are rarely captured in the evaluation of these trials. This qualitative study aimed to capture the experiences of a small research team coordinating a large, multisite implementation trial (the Hide and Seek Project) in the Australian healthcare setting.Design A qualitative approach was used, whereby members of the Hide and Seek Project research team were invited to take part in semistructured focus groups led by an external facilitator. The focus group guide was developed to explore the experiences of the research team (including challenges and lessons learnt) as they moved through key study activities. Focus groups were transcribed verbatim and analysed using an inductive thematic approach. Barriers and facilitators identified within themes were deductively coded to domains of the updated Consolidated Framework for Implementation Research.Setting Participants were recruited from a research organisation based in Sydney, Australia.Participants A total of seven researcher and administering institution participants took part in four focus groups.Results Analysis highlighted the following themes: navigating bureaucracy, distinguishing implementation trials from clinical trials, the impact of COVID-19, balancing rigour and pragmatism in implementation trials, data access and complexity of analysis, and key learnings and future directions (subthemes: building relationships with ethics committees, communicating implementation concepts, streamlining of the implementation and research approach).Conclusions Findings highlight the need for streamlining current administrative and ethical review processes, as well as procedures that allow greater flexibility for researchers to respond to challenges as they arise. Lessons learnt by the Hide and Seek Project team hold potential relevance for fellow researchers involved in coordinating implementation trials across diverse contexts.